Synthesis and characterizations of Al2O3 using Calliandra calothyrsus leaf extract and its potential application for increasing fuel oxidation stability number - Indah Kurniawaty; Yoki Yulizar; Haryo Satriya Oktaviano; Dewangga Oky Bagus Apriandanu (Results in Surfaces and Interfaces, 2025)
Calliandra calothyrsus leaf extract (CLE) successfully produced amorphous and gamma Al2O3 by a simple one-pot method. The secondary metabolites of alkaloids and saponins acted as weak base suppliers and capping agents. The various calcination temperatures resulted in different structures and surface morphologies. The flower-like form of gamma Al2O3 was observed at high temperatures of 700 °C, and 800 °C. As a result, the rod-flake structure of amorphous Al2O3 was obtained at 600 °C according to structural and morphological analysis. Al2O3 with a blended fuel containing Research Octane Number (RON) 95 and 10 % ethanol, as a gasoline model, was employed to analyze the oxidation stability number. Interestingly, Al2O3 calcined at 600 °C has the highest oxidation stability due to the rod shape of amorphous alumina and a higher average pore size confirmed by XRD, SEM and N2 adsorption-desorption analyses. This work demonstrates the preparation of Al2O3 with different phases using plant extract by a simple one-pot green method and its promising application as a fuel additive for increasing oxidation stability numbers.